Efficacy of drip irrigation on summer sesame grown in Narmada district of Gujarat - FADADU, M. H.; SHRIVASTAVA, P K (Journal of Soil and Water Conservation, 2020)
The experiment was conducted to study the effect of different irrigation levels and different dripper discharge rates on sesame crop and to study the effect of irrigation on growth and quality parameters of sesame at the farm of College of Agricultural Engineering and Technology, Dediapada; during summer seasons (Feb.-May) of the years 2018 and 2019. A factorial randomized block design with four replications of the ten treatments consisting of drip irrigation levels, dripper discharge rates and control was adopted for the experiment. The drip irrigation levels selected in the experiment were 1) 0.5 PEF (Pan Evaporation Fraction), 2) 0.75 PEF and 3) 1.0 PEF and the dripper discharge levels selected in the study were 1) 2 LPH 2) 4 LPH and 3) 8 LPH. The irrigation level of 0.75 PEF and dripper discharge of 4 LPH recorded highest plant growth and yield attributes. The pooled data indicated that the irrigation level of 0.75 PEF (I2) recorded the highest plant height (101.1 cm), 1000 seeds weight (4.12 g), oil content of seed (40.11%), plant biomass (1985.72 kg/ha) and yield (1791 kg/ha). The pooled data indicated that the dripper discharge of 4 LPH (D2) recorded the highest plant height (150.67 cm), oil content of seed (39.81%), plant biomass (1825.93 kg/ha) and yield (1484.5 kg/ha). The highest water use efficiency of 2.66 kg/ha mm was obtained in treatment I1D2 followed by water use efficiency of 2.61 kg/ha mm was obtained in I2D2 treatment. The treatment I2D2 recorded highest net return of Rs. 1,19,790 per ha and the treatment control recorded lowest net return Rs. 42,219 per ha